Micro fluidity and macro stability in inventor networks - Michael Fritsch; Muhamed Kudic (Friedrich Schiller University Jena, 2019)
From a macro perspective, inventor networks are characterized by rather stable structures. However, the high levels of fluidity of inventors and their ties found in reality contradicts this macro pattern. In order to explain these contradicting patterns, we zoom in on the intermediate group structures of co-patenting relationships found among inventors in German laser technology research over a period of 45 years. Our findings suggest that continuity of individual actors is not a key factor in maintaining structural stability of networks. Group level explorations indicate that the successor of an existing key player belonged to the exiting key player's ego-network, indicating that the group level provides a source of stability and functionality to the system.
Keywords: D22; D85; L23; O3; 330; Inventor network; network stability; key player analysis; innovation; laser technology